Obesity Mediates the Effect of Past and Current Mental Health on Diabetes Treatment Outcomes - Fatemeh Amini; Afsaneh Khajevand Khoshli; Javanshir Asadi; Adeleh Bahar; Hamid Najafipour; Ali Mirzazadeh (Tehran University of Medical Sciences, 2022)
Background: Anxiety and depression (A&D) are common among patients with diabetes (DM). We assessed the mediatory effect of obesity on the pathway between past and current mental health (as measured by A&D) on self-care DM treatment adherence and DM treatment failure. Methods: We used data collected in two rounds (2009-12, 2014-2018) of a population-based cohort study in Kerman, Iran (KERCADRS). By a random cluster sampling approach, 5900 residents of Kerman aged 15 to 75 yr were recruited to the study to measure demographic characteristics, body measures (to calculate BMI), adherence to DM treatment, and symptoms for A&D (Beck questionnaires). Fasting blood also collected for biochemical tests and glycemic control (as an indicator for treatment failure). We used path analysis and Structural Equation Modeling (SEM) for analysis. Results: We analyzed data for 264 patients with diabetes who attended in both study rounds. While only 5.7% reported not adherence to DM treatment, 67.9% had diabetes treatment failure. Past mental health had a significant positive association with HbA1c (standard beta coefficient for total effect =0.148, P=0.044), of which 42% was indirect effect through obesity. Current mental health had a positive association with current no adherence to diabetes treatment (standard beta coefficient for total effect=0.077, P=0.001). Conclusion: Our study showed an important indirect path from A&D to diabetes treatment failure outcome which mediated by obesity. Screening for A&D symptoms and treating those as well as obesity among patients with diabetes may improve glycemic control.